Karakteristik Potret dalam Seni Tato Realis - Prayoga, I Kadek Dena Ari; Tjokropramono, I Gede Yosef; Putra, I Gede Jaya (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This study aims to analyses the characteristics of portraiture in realistic tattoo art, one of the most popular tattoo styles today. The main focus of this research is to identify the key elements that make portrait tattoos look realistic and lifelike, as well as the techniques used by tattoo artists to achieve these results. This research is part of the MBKM internship report and employs a descriptive qualitative research method. Data were collected through interviews with tattoo artists experienced in the realistic style, direct observation during the tattoo-making process, and photographic documentation of their works. Content analysis was used to identify common features that define realistic portrait tattoos, such as accuracy in capturing facial proportions, placement of light and shadow, and the use of smooth shading gradients to create depth effects, along with attention to small details that enhance the realistic impression.The main findings of this study show that accuracy in depicting facial expressions and skin texture significantly impacts the quality of realistic portrait tattoos. Additionally, a deep understanding of facial anatomy and proficiency in ink application and colour gradients are crucial factors. The implications of this research suggest that mastering these techniques not only improves the quality of tattoos but also promotes the development of the realism style within the tattoo art industry.